2017
DOI: 10.5194/amt-10-4865-2017
|View full text |Cite
|
Sign up to set email alerts
|

A technique for the measurement of organic aerosol hygroscopicity, oxidation level, and volatility distributions

Abstract: Abstract. Hygroscopicity, oxidation level, and volatility are three crucial properties of organic pollutants. This study assesses the feasibility of a novel measurement and analysis technique to determine these properties and establish their relationship. The proposed experimental setup utilizes a cloud condensation nuclei (CCN) counter to quantify hygroscopic activity, an aerosol mass spectrometer to measure the oxidation level, and a thermodenuder to evaluate the volatility. The setup was first tested with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Until recently, this technique has been separately applied to either measurements of composition or hygroscopicity (Hong et al, 2014;Johnson et al, 2004;Sellegri et al, 2008;Villani et al, 2013;Huffman et al, 2008). Three recent studies have combined these measurements by splitting heated samples from a TD between an aerosol mass spectrometer (AMS) and a cloud condensation nuclei (CCN) counter (Cain and Pandis, 2017;Cerully et al, 2015;Hildebrandt Ruiz et al, 2015). Cain andPandis (2017) andHildebrandt Ruiz et al (2015) examined chamber-generated SOA from α-Pinene and toluene respectively, while Cerully et al (2015) performed atmospheric measurements of rural aerosol from the southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, this technique has been separately applied to either measurements of composition or hygroscopicity (Hong et al, 2014;Johnson et al, 2004;Sellegri et al, 2008;Villani et al, 2013;Huffman et al, 2008). Three recent studies have combined these measurements by splitting heated samples from a TD between an aerosol mass spectrometer (AMS) and a cloud condensation nuclei (CCN) counter (Cain and Pandis, 2017;Cerully et al, 2015;Hildebrandt Ruiz et al, 2015). Cain andPandis (2017) andHildebrandt Ruiz et al (2015) examined chamber-generated SOA from α-Pinene and toluene respectively, while Cerully et al (2015) performed atmospheric measurements of rural aerosol from the southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…Three recent studies have combined these measurements by splitting heated samples from a TD between an aerosol mass spectrometer (AMS) and a cloud condensation nuclei (CCN) counter (Cain and Pandis, 2017;Cerully et al, 2015;Hildebrandt Ruiz et al, 2015). Cain andPandis (2017) andHildebrandt Ruiz et al (2015) examined chamber-generated SOA from α-Pinene and toluene respectively, while Cerully et al (2015) performed atmospheric measurements of rural aerosol from the southeastern United States. Across these three cases, a clear relationship between hygroscopicity and oxidation level (often measured as an oxygen to carbon ratio, O : C) could not be established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the least volatile organic compounds were shown to have the lowest hygroscopicity, which contrasts with many previous studies. Cain and Pandis (2017) found that low volatility compounds had typically high O:C ratios, while Hildebrandt observed conflicting trends. Cerully et al 15 (2015) did not report either trend for O:C ratio but found correlation between low volatility and high average carbon oxidation state ( ), an alternate measure of oxidation level (Kroll et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Three recent studies have combined these measurements by splitting heated samples from a TD between an aerosol mass spectrometer (AMS) and a cloud condensation nuclei (CCN) counter (Cain and Pandis, 2017;Cerully et al, 2015;Hildebrandt Ruiz et al, 2015). Cain and Pandis (2017) and Hildebrandt examined chamber-generated SOA from α-pinene and toluene 10 respectively, while Cerully et al (2015) performed atmospheric measurements of rural aerosol from the south-eastern United…”
Section: Introductionmentioning
confidence: 99%